A first book of animals - Davies, Nicola 1958- (Walker Books and subsidiaries, 2016)
Nicola Davies, the award-winning author of A First Book of Nature, presents a spellbinding treasury of poems about the animal world, illustrated in breathtaking detail by Petr Horacek. Polar bears playing on the ice, tigers hunting in the jungle, fireflies twinkling in the evening sky and nightingales singing in the heart of the woods - there are animals everywhere. From blue whales to bumblebee bats and everything in between, A First Book of Animals takes you all over the planet to visit all kinds of different creatures
Includes index
Keywords: Kinderlyrik; Englisch; Tiere; Animals / Poetry; Children's poetry; Animals; Poetry; Children's nonfiction; Children's picture books; Anthologie; Sachbilderbuch; Kindersachbuch